EATING DISORDER-AN ALARMING HEALTH PROBLEM - ELIZABETH, VINITHA; M.SUBHA (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Eating disorders are of serious concern in one's health.It is a psychopathological disorder affecting patient's relationship with foodÂ body manifesting as distorted eating behaviour [1]. It includes anorexia nervosa and bulimia nervosaâ€. Anorexia Nervosa (AN) is a biologically based serious mental disorder with high levels of mortality and disability, physical and psychological morbidity and impaired quality of life. Anorexia Nervosa is the leading cause of disease burden in terms of years of life lost through death or disability. Psychotherapeutic interventions are the treatment of choice, and this depends on the stage of illness [2]. Bulimia Nervosa (BN) has a higher prevalence among women [3,4,5]. This article provides overview of presentation, diagnosis, complications, management and treatment of eating disorders.